Tumor-associated carbonic anhydrase 9 spatially coordinates intracellular pH in three-dimensional multicellular growths. - Swietach, P; Wigfield, S; Cobden, P; Supuran, C; Harris, A; Vaughan-Jones, R (2008)
CA9 is a membrane-tethered, carbonic anhydrase (CA) enzyme, expressed mainly at the external surface of cells, that catalyzes reversible CO(2) hydration. Expression is greatly enhanced in many tumors, particularly in aggressive carcinomas. The functional role of CA9 in tumors is not well established. Here we show that CA9, when expressed heterologously in cultured spheroids (0.5-mm diameter, ~25,000 cells) of RT112 cells (derived from bladder carcinoma), induces a near-uniform intracellular pH (pH(i)) throughout the structure. Dynamic pH(i) changes during displacements of superfusate CO(2) concentration are also spatially coincident (within 2 s). In contrast, spheroids of wild-type RT112 cells lacking CA9 exhibit an acidic core (~0.25 pH(i) reduction) and significant time delays (~9 s) for pH(i) changes in core versus peripheral regions. pH(i) non-uniformity also occurs in CA9-expressing spheroids after selective pharmacological inhibition of the enzyme. In isolated RT112 cells, pH(i) regulation is unaffected by CA9 expression. The influence of CA9 on pH(i) is thus only evident in multicellular tissue. Diffusion-reaction modeling indicates that CA9 coordinates pH(i) spatially by facilitating CO(2) diffusion in the unstirred extracellular space of the spheroid. We suggest that pH(i) coordination may favor survival and growth of a tumor. By disrupting spatial pH(i) control, inhibition of CA9 activity may offer a novel strategy for the clinical treatment of CA9-associated tumors.